Polymers on nanoparticles: structure & dynamics. Issue 6 (18th January 2019) - Hore, Michael J. A.
Abstract : Grafting polymers to nanoparticle surfaces influences properties from the conformation of the polymer chains to the dispersion and assembly of nanoparticles within a polymeric material. Abstract : Grafting polymers to nanoparticle surfaces influences properties from the conformation of the polymer chains to the dispersion and assembly of nanoparticles within a polymeric material. Recently, a small body of work has begun to address the question of how grafting polymers to a nanoparticle surface impacts chain dynamics, and the resulting physical properties of a material. This Review discusses recent work that characterizes the structure and dynamics of polymers that are grafted to nanoparticles and opportunities for future research. Starting from the case of a single polymer chain attached to a nanoparticle core, this Review follows the structure of the chains as grafting density increases, and how this structure slows relaxation of polymer chains and affects macroscopic material properties.